Assessment of farmer preferences for cattle traits in smallholder cattle production systems of Kenya and Ethiopia - Ouma, Emily A.; Abdulai, A.; Drucker, Adam G.; Obare, G.A. (University of Kiel, 2004)
The urgent need to improve livestock productivity in sub.Saharan Africa in order to keep pace with expected increases in demand for meat and milk is very topical. Breed improvement provides key entry points for increasing productivity in cattle populations. However, there are tendencies for genetic improvement programs to focus on single, market driven traits such as milk or meat production in isolation of environmental constraints and broader livestock system functions which cattle perform in developing countries. This potentially leads to genotypes that are not well adapted to the environment and not capable of performing the multiple roles that cattle assume in smallholder systems. In developing countries, many important functions of livestock are embedded in non-tradeable traits that are neither captured in economic analysis nor considered in livestock improvement programs. This study employs Participatory Rural Appraisal (PRA) ranking techniques and conjoint analysis to evaluate preferences of cattle keepers in pastoral and agro-pastoral systems of selected sites in Kenya and Ethiopia for various cattle traits. These systems are characterized by low input management and prevalence of various cattle diseases. Trypanosomosis is a serious disease constraint in Ghibe valley of Ethiopia and some of the pastoral areas in Kenya. The results indicate that farmer preferences for cattle traits are influenced by various factors including production system characteristics, infrastructural constraints and environmental conditions, especially in relation to disease prevalence and availability of cattle feeds. In the crop-livestock systems of Ghibe valley in Ethiopia, preferred cattle traits include trypanotolerance, reproductive potential and fitness to traction. Milk production is a less important trait. On the other hand, in the pastoral and agropastoral systems of Kenya, important traits include trypanotolerance, reproductive potential, coat colour and watering needs.